2000
DOI: 10.1136/jme.26.6.444
|View full text |Cite
|
Sign up to set email alerts
|

Consumerism in prenatal diagnosis: a challenge for ethical guidelines

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Some authors have coined the expression 'prenatal consumerism' [36] to describe this tendency, but other Modified from Bellieni et al [11]. * p = 0.0018; ** p < 0.01; *** p < 0.001; **** p < 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have coined the expression 'prenatal consumerism' [36] to describe this tendency, but other Modified from Bellieni et al [11]. * p = 0.0018; ** p < 0.01; *** p < 0.001; **** p < 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…There has been significant discussion in many countries and by the World Health Organization regarding the limitation of prenatal testing and assisted reproductive options such as preimplantation genetic diagnosis (PGD) to severe diseases that will have a large and immediate impact on the health of the child. 43,44 Still, genetic selection for 'benign' traits has been deemed acceptable under certain conditions including benefit to the child, equal access to services, and the absence of clear disadvantage. 45 There are several ethical dilemmas inherent to limiting genetic testing for reproductive purposes (prenatal testing for PDG), and the line between disease and trait can be blurred.…”
Section: Discussionmentioning
confidence: 99%
“…Some experts see non-DNA related procedures (e.g., ultrasound) as genetic technologies because, as earlier research has shown (Ettorre, 2002), these are linked procedurally in reproductive medicine. It has been argued that prenatal technologies are ethically the most difficult applications of genetics (Henn 2000).…”
Section: What Are Prenatal Genetic Technologies?mentioning
confidence: 99%